Highly enhanced oxidation of arsenite at the surface of birnessite in the presence of pyrophosphate and the underlying reaction mechanisms. (15th December 2020) - Ying, Chaoyun; Lanson, Bruno; Wang, Cheng; Wang, Xiaoming; Yin, Hui; Yan, Yupeng; Tan, Wenfeng; Liu, Fan; Feng, Xionghan
Highlights: As(III) oxidation by birnessite leads to Mn(II/III) species formation. Manganite precipitation passivates birnessite surface and limits As(III) oxidation. Presence of pyrophosphate in reactive medium enhances As(III) oxidation. PP inhibits passivation forming soluble Mn(III) complexes. Oxidation enhancement by chelates depends on the stability of Mn(III) complexes. Abstract: Manganese(IV) oxides, and more especially birnessite, rank among the most efficient metal oxides for As(III) oxidation and subsequent sorption, and thus for arsenic immobilization. Efficiency is limited however by the precipitation of low valence Mn (hydr)oxides at the birnessite surface that leads to its passivation. The present work investigates experimentally the influence of chelating agents on this oxidative process. Specifically, the influence of sodium pyrophosphate (PP), an efficient Mn(III) chelating agent, on As(III) oxidation by birnessite was investigated using batch experiments and different arsenic concentrations at circum-neutral pH. In the absence of PP, Mn(II/III) species are continuously generated during As(III) oxidation and adsorbed to the mineral surface. Field emission-scanning electron microscopy, synchrotron-based X-ray diffraction and Fourier transform infrared spectroscopy indicate that manganite is formed, passivating birnessite surface and thus hampering the oxidative process. In the presence of PP, generated Mn(II/III) species form soluble complexes, thus inhibiting surface passivation and promoting As(III) conversion to As(V) with PP. Enhancement of As(III) oxidation by Mn oxides strongly depends on the affinity of the chelating agent for Mn(III) and from the induced stability of Mn(III) complexes. Compared to PP, the positive influence of oxalate, for example, on the oxidative process is more limited. The present study thus provides new insights into the possible optimization of arsenic removal from water using Mn oxides, and on the possible environmental control of arsenic contamination by these ubiquitous nontoxic mineral species. Graphical abstract: Image, graphical abstract